دراسة كفاءة البارابينات من الناحية الميكروبيولوجية والكيميائية في نموذج من القطورات العينية المصنعة محلياً - مرعي منى; داؤد نزيه; وليد محمد فيصل (Latakia University Journal -Medical Sciences Series, 2019)
تعد البارابينات من أكثر المواد الحافظة استخداماً في القطورات العينية وهي فعالة ضد الجراثيم إيجابية الغرامGr+ وفعالة ضد الفطور والخمائر (Soni,2005)ولكنها ضعيفة الفعالية ضد الجراثيم سلبية الغرام Gr- مثل الزائفة الزنجارية (Fraise,2004). هدفت هذه الدراسة إلى تقييم كفاءة البارابينات ميكروبيولوجياً وكيميائياً في نموذج من قطورات عينية محلية الصنع. شملت هذه الدراسة 45 قطرة عينية من السوق المحلية من نفس النوع ومن نفس الشركة حاوية على البارابينات كمواد حافظة وهي النيباجين والنيبازول، درست عقامة هذه القطورات ثم طبّق عليها اختبار التحدّي Challenge test، وتم حساب التركيز الأصغري المثبط MIC)) من البارابينات العيارية (النيباجين والنيبازول)، وحساب تركيز البارابينات في القطورات المدروسة. أجريت الاختبارات السابقة في مخبر الجراثيم في كلية الصيدلة، جامعة تشرين، في الفترة الواقعة بين حزيران 2010 إلى أيلول 2011. ظهر لدينا نمو جرثومي عائد للمكورات العنقودية البشروية في قطرة واحدة من القطورات المدروسة (2.22%) وبعد إجراء التحاليل الكيميائية لحساب تركيز البارابينات المستخدمة في هذه القطرة تبين انخفاض تركيزها بمعدل 10.3% عن التركيز المصرح به على العبوة، أما التركيز في باقي القطورات فكان مطابقاً للتركيز المصرح به. أظهرت نتائج اختبار التحدي أن البارابينات الموجودة في القطورات المدروسة كانت مطابقة للشروط المرجعية بالنسبة لكل من المكورات العنقودية الذهبية والمكورات الأحادية والايشيرشيا المعوية، بينما لم تطابق شروط اختبار التحدي بالنسبة للزائفة الزنجارية. كانت قيم MIC بالنسبة للبارابينات العيارية هي 0.0495% بالنسبة للمكورات العنقودية الذهبية، و 0.066% بالنسبة لكل من المكورات الأحادية والايشيرشيا المعوية والزائفة الزنجارية. Background: The Parabens are the most preservatives used in ophthalmic drops. These preservatives are effective against Gram-positive bacteria, fungi and yeasts (Soni,2005). However, they are weak against Gram-negative bacteria such as Pseudomonas aeruginosa (Fraise, 2004). The aim of this study was to assess the antimicrobial and chemical efficiency of the Parabens in a one type of local produced eye drops. Materials and methods: A total of 45 samples of one type of eye drops were collected from the local market (from the same pharmaceutical company). These eye drops contain Parabens as preservatives (Nipasol- Nipagin). All samples were tested by their sterility and then subjected to the challenge test. In addition, the minimal inhibitory concentrations (MIC) of standard (Nipasol-Nipagin) were calculated as well as determination of the concentration of the Parabens in these samples. All tests were carried off in laboratory of microbiology in the College of Pharmacy-University of Tishreen, during a period of June 2010 to September 2011. Results: Bacterial growth ( staphylococcus epidermidis ) appeared in one drop sample of eye drops studied (2.22%). However, chemical analysis of the Parabens found in this contaminated drop showed decreasing as low as 10.3% of the authorized concentration on the package. the Parabens concentration in the rest of eye drops were identical to authorized concentrations. The results of the challenge test showed that the Parabens used in eye drops studied were identical to the related reference studies for staphylococcus aureus, Micrococcus luteus and Escherichia coli, but not for Pseudomonas aeruginosa. The MIC values ​​for the standard Parabens were 0.0495% for staphylococcus aureus, and 0.066% for all Micrococcus luteus, Escherichia coli and Pseudomonas aeruginosa.